2023
DOI: 10.1039/d3ta01021j
|View full text |Cite
|
Sign up to set email alerts
|

3D printing of solvent-treated PEDOT:PSS inks for electromagnetic interference shielding

Abstract: 3D printing of conducting polymers has been achieved very recently by direct ink writing of poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS)-based inks. This field is in its infancy, calling for further research to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…The EMI Shielding performance was further evaluated after an interval of 30 days and the value remained same indicating that PEDOT: PSS -PEO-PVA blend had high stability. [80] Ghaderi et al [148] prepared EMI shields in X-band through 3D printing of solvent-treated PEDOT:PSS inks via molecular engineering by co-solvent doping or solvent post-treatment with Figure 8. Schematic illustration of the procedure for preparing PMIA/Ag NWs/PEDOT: PSS nonwoven fabric.…”
Section: Pedot: Pss Based Composites Without Fillers For Emi Shieldingmentioning
confidence: 99%
See 2 more Smart Citations
“…The EMI Shielding performance was further evaluated after an interval of 30 days and the value remained same indicating that PEDOT: PSS -PEO-PVA blend had high stability. [80] Ghaderi et al [148] prepared EMI shields in X-band through 3D printing of solvent-treated PEDOT:PSS inks via molecular engineering by co-solvent doping or solvent post-treatment with Figure 8. Schematic illustration of the procedure for preparing PMIA/Ag NWs/PEDOT: PSS nonwoven fabric.…”
Section: Pedot: Pss Based Composites Without Fillers For Emi Shieldingmentioning
confidence: 99%
“…Ghaderi et al. [ 148 ] prepared EMI shields in X‐band through 3D printing of solvent‐treated PEDOT:PSS inks via molecular engineering by co‐solvent doping or solvent post‐treatment with DMSO, EG, DMF, methanol and ethanol. It was found that on doping or post treatment, EMI shielding property got improved due to increased electrical conductivity as compared to the pristine PEDOT: PSS.…”
Section: Pedot: Pss Based Composites For Emi Shieldingmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, mainstream EMI shielding materials include intrinsic conductive polymers (polypyrrole, polyaniline, and polythiophene), carbon-based materials (CNTs, graphene, , rGO, and carbon black), metallic nanomaterials (copper nanofilm, silver nanowires, , and silver nanoparticles), and two-dimensional (2D) transition metal carbides and/or nitrides (MXene). , However, whatever the compositions are, compact shielding materials with higher electromagnetic loss are usually accompanied by higher electrical conductivity. , The inherent high electrical conductivity leads to intense electromagnetic reflection, especially for millimeter and submillimeter waves, at the surface of the material. Once the reflected waves return to the environment, intense secondary radiation is generated, which causes more serious EM pollution and environmental problems.…”
Section: Introductionmentioning
confidence: 99%
“…12 The thermal and nonthermal effects of high-power THz waves and water may cause thermal damage to cells, destroy the repair mechanism of cells, even induce cell death, and greatly increase the probability of canceration. 13 Until now, mainstream EMI shielding materials include intrinsic conductive polymers (polypyrrole, 15 polyaniline, 16 and polythiophene 17 ), carbon-based materials (CNTs, 18 graphene, 19,20 rGO, 20−22 and carbon black 23 ), metallic nanomaterials (copper nanofilm, 24 silver nanowires, 25,26 and silver nanoparticles 27 ), and two-dimensional (2D) transition metal carbides and/or nitrides (MXene). 28,29 However, whatever the compositions are, compact shielding materials with higher electromagnetic loss are usually accompanied by higher electrical conductivity.…”
Section: ■ Introductionmentioning
confidence: 99%